Pediatric Rheumatology - Martini, Alberto; Spencer, Charles; Edwards, Dawn
Pediatric Rheumatology is the official publication of the Pediatric Rheumatology European Society (PReS). Submissions on the evaluation and treatment of non-surgical musculoskeletal syndromes and diseases in children and adolescents, particularly autoimmune and rheumatic diseases are welcomed. Diseases and syndromes of particular interest include musculoskeletal pain syndromes, rheumatic fever and post-streptococcal syndromes, juvenile idiopathic arthritis, systemic lupus erythematosus, juvenile dermatomyositis, local and systemic scleroderma, Kawasaki disease, Henoch-Schonlein purpura and other vasculitides, sarcoidosis, inherited musculoskeletal syndromes, autoinflammatory syndromes, and others. Pediatric Rheumatology encourages submissions on educational advances, drug studies, laboratory and radiological evaluations, and outcome measures. Pediatric Rheumatology began publishing as Pediatric Rheumatology Online Journal in 2003. For access to articles published prior to 2006, contact the Editorial team. PReS are providing financial support to aid any authors who require assistance with the article processing charge (APC). Applicable authors would be charged a discounted article processing charge of £350 payable for articles accepted for publication.Authors who would like to apply for the reduced APC should contact the contact the Editorial team. Applicable authors can request this support during the submission process, stating payment via the PReS Shared Support option.